2019
DOI: 10.18677/encibio_2019a163
|View full text |Cite
|
Sign up to set email alerts
|

Pré-Natal Masculino: A Importância Da Participação Do Pai Nas Consultas De Pré-Natal

Abstract: RESUMOObjetivou-se com este estudo analisar a importância da participação do pai nas consultas de pré-natal. Trata-se de uma revisão integrativa da literatura, de caráter descritivo e exploratório, realizada nas bases de dados da Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS); Banco de Dados de Enfermagem (BDENF) e Scientific Electronic Library Online (SCIELO). Incluíram-se estudos primários, publicados em português, inglês e espanhol, disponíveis na íntegra, entre os anos 2008 e 2018. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
20

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 11 publications
0
1
0
20
Order By: Relevance
“…12 It is noteworthy that the father's participation in prenatal care brings numerous benefits for the pregnant woman and her family, as it prepares the man to experience the birth, contributing to the establishment of the father and child bond; favors the social and emotional support of the companion to the pregnant woman, facilitates learning to care for the mother and baby; assists in preparation for childbirth; strengthens the relationship between the couple and their ability to make choices, helping the companion in pregnancy, childbirth and postpartum and increases the woman's satisfaction with the support received from her partner during labor. 13 Systematic review including studies conducted in nine countries identified that interventions conducted with men in maternal and newborn health increased couple communication and joint decision making, with ambiguous effects on women's autonomy their findings therefore recommend the involvement of men as a health promotion strategy. They emphasize, however, that interventions for this purpose must be carefully planned so that potential detrimental effects on the dynamics of the couple's relationship can be mitigated.…”
Section: Discussionmentioning
confidence: 99%
“…12 It is noteworthy that the father's participation in prenatal care brings numerous benefits for the pregnant woman and her family, as it prepares the man to experience the birth, contributing to the establishment of the father and child bond; favors the social and emotional support of the companion to the pregnant woman, facilitates learning to care for the mother and baby; assists in preparation for childbirth; strengthens the relationship between the couple and their ability to make choices, helping the companion in pregnancy, childbirth and postpartum and increases the woman's satisfaction with the support received from her partner during labor. 13 Systematic review including studies conducted in nine countries identified that interventions conducted with men in maternal and newborn health increased couple communication and joint decision making, with ambiguous effects on women's autonomy their findings therefore recommend the involvement of men as a health promotion strategy. They emphasize, however, that interventions for this purpose must be carefully planned so that potential detrimental effects on the dynamics of the couple's relationship can be mitigated.…”
Section: Discussionmentioning
confidence: 99%
“…É importante pensar e organizar previamente ações que possam sanar as dúvidas presentes do casal em relação à gestação e fornecer orientações sobre legislação de apoio para dar suporte adequado que homem e mulher necessitam, buscando a conscientização masculina e viabilizando sua presença dentro dos serviços de saúde nas consultas de pré-natal. (13)(14).…”
Section: A Gente Tenta Fazer Com Que Ele Fique Feliz (E11)unclassified
“…Historicamente, tanto o planejamento reprodutivo quanto às ações em saúde voltadas ao momento da gestação, parto e puerpério foram pensadas e direcionadas às mulheres e às gestantes, enfocando o binômio mãe-criança. No entanto, nos últimos anos, não só no Brasil, mas em outros países também, tem se discutido sobre a importância do envolvimento ativo do pai/parceiro em todas as fases da gestação (Brasil, 2016;Mendes & Santos, 2019).…”
Section: Introductionunclassified